2001
DOI: 10.1128/jvi.75.8.3613-3625.2001
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of p21 cip1 in Cells Productively Infected with Human Cytomegalovirus

Abstract: Human cytomegalovirus (HCMV) stimulates arrested cells to enter the cell cycle by activating cyclindependent kinases (Cdks), notably Cdk2. Several mechanisms are involved in the activation of Cdk2. HCMV causes a substantial increase in the abundance of cyclin E and stimulates translocation of Cdk2 from the cytoplasm to the nucleus. Further, the abundance of the Cdk inhibitors (CKIs) p21 cip1/waf1 (p21 cip1 ) and p27 kip1 is substantially reduced. The activity of cyclin E/Cdk2 increases as levels of CKIs, parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
79
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(83 citation statements)
references
References 91 publications
4
79
0
Order By: Relevance
“…Initially, p21CIP1 protein levels are maintained within infected cells up to 9 hpi (42, 71) and then begin to decrease. Regulation occurs at the levels of both transcriptional control and protein degradation (71). Here, we demonstrate that steady-state p21CIP1 protein expression is maintained in the absence of pUL29/28 ( Fig.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Initially, p21CIP1 protein levels are maintained within infected cells up to 9 hpi (42, 71) and then begin to decrease. Regulation occurs at the levels of both transcriptional control and protein degradation (71). Here, we demonstrate that steady-state p21CIP1 protein expression is maintained in the absence of pUL29/28 ( Fig.…”
Section: Discussionmentioning
confidence: 68%
“…Expression of p21CIP1 was previously demonstrated to be tightly regulated during infection (71). p21CIP1 contributes to HCMV IE gene expression during infection of cells in G 2 /M (24).…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have shown that HCMV infection of permissive cells increases the level of p53 and phospho-Ser 15 p53 (17,24,35,48,55), but the levels of p21 decreased (10,40). The IE86 protein of HCMV also increases the level of p53 and interacts with p53 (3,8,55,58).…”
Section: Resultsmentioning
confidence: 91%
“…However, HCMV infection affects p53 because the cellular protein is sequestered in the nucleus in viral replication centers (17). Although the viral IE86 protein stabilizes p53 and activates p21, other proteins specified by the virus must inactivate p53 because HCMV infection causes a decrease in p21 levels (10,40).…”
Section: Discussionmentioning
confidence: 99%
“…Calpains, in particular, are activated during HCMV infection and underlie modulation of the cell cycle regulator p21 cip1 (15). Although constitutive proteasome constituents remain unaltered or increase during infection, immunoproteasome subunits LMP2, MECL1, and LMP7 are specifically downmodulated (33).…”
mentioning
confidence: 99%